Organizational Readiness for Community Health Worker Workforce Integration Among Medicaid Contracted Health Plans and Provider Networks: An Arizona Case Study - Sabo, Samantha; Wexler, Nancy; O'Meara, Louisa; Dreifuss, Heather; Soto, Yanitza; Redondo, Floribella; Carter, Heather; Guernsey de Zapien, Jill; Ingram, Maia (Frontiers in Public Health, 2021)
Understanding and building organizational capacity for system change and the integration of the Community Health Worker (CHW) workforce within the health scare sector requires a supportive organizational culture among sector leaders and providers. The aim of this mixed-methods study was to assess organizational readiness for CHW workforce integration into Arizona Medicaid health systems and care teams. This collaborative effort was in direct response to emergent state and national CHW workforce policy opportunities, and the shifting health care landscape in Arizona – which merged behavior and physical health. Specifically, and in collaboration with a broad-based, statewide CHW workforce coalition, led by the CHW professional association, we assessed 245 licensed health care professionals with experience working with CHWs and 16 Medicaid-contracted health plan leadership. Our goal was to generate a baseline understanding of the knowledge, attitudes and beliefs these stakeholders held about the integration of CHWs into systems and teams. Our findings demonstrate a high level of organizational readiness and action toward integration of CHWs within the Arizona health care system and care teams. CHWs have emerged as a health care workforce able to enhance the patient experience of care, improve population health, reduce cost of care, and improve the experience of providing care among clinicians and staff.